Assessment of fundamental movement skills in Australian children: The validation of a fundamental motor skills quotient (FMSQ) / B Hands and F McIntyre - Hands, B; McIntyre, F (Faculty of Sports Science and Recreation, 2015)
The development of proficient fundamental movement skills (FMS) in children is important for physical, cognitive and social development, and to establish a foundation for an active lifestyle. Many teachers, coaches and physical activity program deliverers use real time observation of individual skill performances during physical activities to assess proficiency in young children. However, a valid method to quantify these observations to provide an overall motor competence is not available. Design: A small pilot validation study using the Bland Altman method to compare scores on the McCarron Assessment of Neuromuscular Development (MAND) and a Fundamental Movement Skill Quotient (FMSQ) (M = 100, SD = 15) derived from a composite score for the observed mastery of 4 skills. Methods: Motor competence in 50 children aged between 7 and 8 years was determined using the MAND. These scores were compared to a FMSQ derived from observation scores for the run, hop, overhand throw and jump. Results: The correlation between the two scores was moderate (r = .35, p = .013) and the level of agreement using the Bland Altman method was acceptable. Conclusions: The FMSQ is a valid measure of motor competence when observing and teaching fundamental motor skills in young children.